Sequences with Random Indice in Classical Banach Space - Gurcan, Mehmet; Calik, Sinan; Gural, Yunus (E D P Sciences, 2017)
In this study we define sequences with random indice in classical Banach space and analyzing it's some properties. After then we define differences sequence space on sequences with random indice. The difference operation is based on indice, and the generated difference sequence has a free stepwise. And here an important definition is the embedding space. Consequently we showed that l(infinity) is a embedding space to c.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY